Sustainable Ethanol Production From Sugarcane Molasses by Saccharomyces cerevisiae Immobilized on Chitosan-Coated Manganese Ferrite - Núñez Caraballo, Arianna; Iliná, Anna; Ramos González, Rodolfo; Aguilar, Cristóbal N.; Michelena Álvarez, Georgina; Flores Gallegos, Adriana Carolina; Sandoval-Cortés, José; Aguilar-Gonzalez, Miguel A.; Soto-Cruz, Nicolas Oscar; García García, José Daniel; Martínez-Hernández, José L. (Frontiers in Sustainable Food Systems, 2021)
The interaction between nanostructures and yeast cells, as well as description of nanoparticles effect on ethanol production are the open questions in the development of this nanobiotechnological process. The objective of the present study was to evaluate the production of ethanol from Saccharomyces cerevisiae when it is found free and immobilized in manganese ferrite coated with chitosan using blackstrap molasses as carbon sources. The coprecipitation method was used to obtain the manganese ferrite coated with chitosan, characterized by X-ray diffraction obtaining the typical diffraction pattern and the crystal size was calculated by the Scherrer's equation as 15.2 nm. The kinetics of sugar consumption and ethanol production were evaluated by HPLC, obtaining in the immobilized system a concentration of 56.15 g/L of ethanol while in the free system 39.1 g/L was obtained for a time of 24 hours, with a reduction observed of time and an increase of ethanol with the presence of nanoparticles, in the consumption of sugars the influence of the invertase enzyme is observed when unfolding the sucrose, in this the immobilized system has faster consumption than in the free system.